Biomonitoring of bisphenol A, triclosan and perfluorooctanoic acid in hair samples of children and adults. Issue 8 (3rd May 2018) - Karzi, Vasiliki; Tzatzarakis, Manolis N.; Vakonaki, Elena; Alegakis, Thanasis; Katsikantami, Ioanna; Sifakis, Stavros; Rizos, Apostolos; Tsatsakis, Aristidis M.
Abstract: Bisphenol A (BPA), triclosan (TCS) and perfluorooctanoic acid (PFOA) are endocrine disruptors linked with negative health effects such as developmental, reproductive and cardiovascular toxicity. The aim of this study was to determine simultaneously the concentration of BPA, TCS and PFOA in hair from children and adults and examine possible associations between biomonitoring data and age, gender, dietary habits and body mass index. Methanolic extraction was applied and the compounds were determined by liquid chromatography–mass spectrometry. Low levels of exposure to PFOA were detected for children and adults at concentrations below limit of quantification. The mean concentration of BPA in children and adults was 20.6 and 16.6 pg mg −1, while for TCS 275.2 and 687.0 pg mg −1, respectively. Children were highly exposed to BPA relative to adults ( P  = .011) although adults had greater exposure to TCS ( P  = .003). Hair from girls had a greater burden of BPA ( P  = .06) compared to boys. Moreover, higher TCS levels were depicted for females in both examined groups (children P  = .200 and adults P  = .213) compared to males, but no statistical differences were observed. Significant differences were also observed between age groups ( P  = .0007) for TCS. No correlations were found between BPA or TCS levels and body mass index or dietary habits for both children and adults. Children have a greater exposure to BPA compared to adults, whereas exposure of adults to TCS seems to be higher than that in children and elderly people. Exposure to BPA occurs mainly via ingestion whereas exposure to TCS mainly via dermal absorption. Abstract : The aim of this study was to determine simultaneously the concentration of bisphenol A (BPA), triclosan (TCS) and perfluorooctanoic acid in hair from children and adults and examine possible associations between biomonitoring data and demographic or somatometric characteristics. Detected perfluorooctanoic acid concentrations were below limit of quantification. Children were highly exposed to BPA while adults were highly exposed to TCS. Hair from girls had a greater burden to BPA, while higher TCS levels were depicted for females in both groups. Moreover, significant differences were observed between age groups for TCS. No correlations were found between BPA and TCS and body mass index or the dietary habits for both groups.